(untitled) (Muitas Vozes, 2021)
In this essay, which combines different textual genres and voices, I present a situated re ection on the potential of queer praxiologies and literacies in the critical elaboration of these dark times, marked by social crises that have stimulated the circulation of authoritarian and neo-fascist repertoires, as well as the banality of evil and life in Brazil. Based on my memories of some political events that took place in the country between 2013 and 2020, and in uenced by the border movements fostered by the idea of praxiological lth, I propose the queering of a set of speech acts and binary oppositions that have produced and crossed this crisis scenario. Next, I share some considerations on the work with queer literacies, which are exempli ed by two experiences at an Institute of Higher Education in the city of Goiânia-GO, Brazil. To conclude, I present my notion of queer literacies as counterpolitics, that is, as a site for the construction of affective resistances to institutionalized political projects that (re)produce frames of authoritarianism, violence, and death.